2020
DOI: 10.3389/fendo.2020.00119
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Knowledge of Candidate Genes Acting at the Beta-Cell Level in the Pathogenesis of T1DM

Abstract: T1DM (type 1 diabetes mellitus), which results from the irreversible elimination of beta-cells mediated by autoreactive T cells, is defined as an autoimmune disease. It is widely accepted that T1DM is caused by a combination of genetic and environmental factors, but the precise underlying molecular mechanisms are still unknown. To date, more than 50 genetic risk regions contributing to the pathogenesis of T1DM have been identified by GWAS (genome-wide association studies). Notably, more than 60% of the identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 110 publications
0
30
0
1
Order By: Relevance
“…Currently, the combination of susceptible genes and islet autoantibodies is the most useful biomarker to predict T1DM risk (63). Previous studies have identified more than 50 candidate loci; a minority of genes (HLA) have large effects, but a majority of these genes have small effects (2). HLA genes confer the greatest risk for the development of T1DM, and the HLA-DR (DR3/4) and HLA-DQ (DQ8) genotypes are mostly used to predict the risk of developing islet autoimmunity (64,65).…”
Section: Exosomes As Novel Biomarkers Of T1dmmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the combination of susceptible genes and islet autoantibodies is the most useful biomarker to predict T1DM risk (63). Previous studies have identified more than 50 candidate loci; a minority of genes (HLA) have large effects, but a majority of these genes have small effects (2). HLA genes confer the greatest risk for the development of T1DM, and the HLA-DR (DR3/4) and HLA-DQ (DQ8) genotypes are mostly used to predict the risk of developing islet autoimmunity (64,65).…”
Section: Exosomes As Novel Biomarkers Of T1dmmentioning
confidence: 99%
“…Type 1 diabetes mellitus (T1DM) is an autoimmune disorder characterized by beta-cell dysfunction and death caused by autoreactive T cells, an absolute lack of insulin, and elevated blood glucose levels (1)(2)(3). Persistent hyperglycemia leads to the development of life-threatening diabetesassociated complications such as blindness, stroke, kidney diseases, and heart diseases, thus decreasing the quality of life of patients and imposing a considerable economic burden on society and individuals.…”
Section: Introductionmentioning
confidence: 99%
“…IL-1β induces the migration of proinflammatory cells into pancreatic islets, mediates cytokine-induced beta-cell apoptosis, exerts direct cytotoxic effects on beta-cells, and may function as inflammatory signal in the early stage of T1DM (102,104,105). IL-1β levels are increased in both patients with a new T1DM diagnosis and patients with chronic T1DM compared with healthy controls, and after treatment, IL-1β levels are decreased in patients who have been newly diagnosed with T1DM (106)(107)(108).…”
Section: The Nlpr3 Inflammasome and T1dmmentioning
confidence: 99%
“…In addition, the sensitive mice showed more substantial islet mass reduction and islet degeneration, as well as more extensive inflammatory infiltration in the pancreatic islets compared with those in the tolerant mice ( Figure 1 ). It is well recognized that both genetic and environmental factors are responsible for the development and progression of T1DM [ 2 , 6 ]. Thus, these results indicated that one or more potential target(s) might be involved in the delayed progression of T1DM among the tolerant mice through the protection of pancreatic β -cell function.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that both genetic and environmental factors are responsible for the pathogenesis and progression of T1DM [ 6 ]. However, the particular causes and precise pathogenic mechanisms of this disease are not completely understood.…”
Section: Introductionmentioning
confidence: 99%